Transforming campus mobility: the DigiSticker system in digital parking solutions - Md. Mojnur, Rahman; Sarker, Md. Tanjil; Mohd-Isa, Wan-Noorshahida; Al Farid, Fahmid; Sheam, Md. Rakibul Hassan; Abdul Karim, Hezerul; Ramasamy, Gobbi; Ali, Aziah (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
University digital parking systems have several benefits and solve many problems with traditional parking. Universities without a digital parking system face restricted parking, traffic congestion, inefficient space utilization, security issues, limited decision-making data, and diminished sustainability initiatives. This study paper discusses the benefits of digital parking systems and the drawbacks of traditional methods. By using technology to streamline university parking administration, the DigiSticker system offers an innovative solution. The DigiSticker system improves parking efficiency, convenience, and security for students, professors, and staff by delivering real-time parking information, assistance, and automated payments. This system has a user-friendly website and mobile app, fast registration, gate access management, security, user experience enhancement, and sustainability. Universities can improve student and staff parking experiences while improving parking management efficiency, security, and sustainability by meeting these requirements.